El "cuerpo acción" en el arte para todos. Tenemos: cara, ombligo y dedos de los pies - Miguel Álvarez, Laura De (Arte, Individuo y Sociedad, 2007)
In the same way as our ancestors did, human beings nowadays have the primary instinct to communicate. Early humans did it through ritual paintings on the walls of the places they lived in. The existence of these human tracks constitutes the only evidence that we now, thousands of years later, have of their presence in these locations. Modern humans, in many cases, have not yet found the way to express themselves without using their voice. We recognize parts of our own body (mainly the hand) in the tracks that have appeared in different archaeological sites. Therefore we can understand the instinct to represent the handprint as a form of expression that comes from the human necessity to transmit something, even if still undetermined. Ever since the first artistic manifestations appeared with the body as undisputable protagonist of the creation and artistic expression, we started leaving aside, little by little, that indispensable tool which kept both the creator and the created object linked together. For a while we gradually became detached of our own corporeal nature and so, in close contact with matter, gave free rein to humans creative artistic capacity. Eventually, the body retakes again its importance and it reappears as the star element in the act of an artwork creation. This happened thanks to the importance of the presence of the artist body in works that fall within the Abstract Expressionism movement or the Austrian one known as Viennese Actionism. In this way and inspired both by Ives Klein anthropometries, as well as the tracks of our prehistoric ancestors, we design an artistic ludic activity. In this activity we work with 75 subjects who live and coexist in our present society. The results and evaluation of these results, obtained from the experience that includes the activity 'We have: face, navel and toes', allow us to give answers to the questions that are considered at the beginning of this Research Work.